2016
DOI: 10.1177/0267658316673403
|View full text |Cite
|
Sign up to set email alerts
|

Phrase frequency, proficiency and grammaticality interact in non-native processing: Implications for theories of SLA

Abstract: This study reports on a self-paced reading experiment in which native and non-native speakers of English read sentences designed to evaluate the predictions of usage-based and rule-based approaches to second language acquisition (SLA). Critical stimuli were four-word sequences embedded into sentences in which phrase frequency and grammaticality were crossed in order to examine whether grammatical processing is modulated by phrase frequency. The magnitude of grammaticality effects for native speakers did not di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
23
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(25 citation statements)
references
References 48 publications
2
23
0
Order By: Relevance
“…Moreover, generative approaches are better at connecting properties that are superficially unrelated but underlyingly linked to the same parameter, for example, properties that emerge at the same time in development (Snyder, 2001), precisely because the granularity of the formal theory employed can account for this and, in fact, even predicts this. There remain plenty of properties that allow a head-to-head framework comparison, see specifically Shantz (2017) and Zyzik (2017) for some good examples. Where we differ incommensurably is in delineating the parts of language that are claimed to be truly universal and otherwise unacquirable, that is, PoS properties illustrating the logical problem of acquisition.…”
Section: Conclusion: a Place For Multiple Theories In Slamentioning
confidence: 99%
“…Moreover, generative approaches are better at connecting properties that are superficially unrelated but underlyingly linked to the same parameter, for example, properties that emerge at the same time in development (Snyder, 2001), precisely because the granularity of the formal theory employed can account for this and, in fact, even predicts this. There remain plenty of properties that allow a head-to-head framework comparison, see specifically Shantz (2017) and Zyzik (2017) for some good examples. Where we differ incommensurably is in delineating the parts of language that are claimed to be truly universal and otherwise unacquirable, that is, PoS properties illustrating the logical problem of acquisition.…”
Section: Conclusion: a Place For Multiple Theories In Slamentioning
confidence: 99%
“…This special issue includes two articles taking a formal approach (Yang and Montrul, 2017, this issue; Bardovi-Harlig and Stringer, 2017, this issue), two articles taking a functional approach (Zyzik, 2017, this issue; Paquot, 2017, this issue), and one article testing both approaches (Shantz, 2017, this issue).…”
Section: The Articlesmentioning
confidence: 99%
“…Another linguistic area of where research is converging is what is called ‘semi-productive’ linguistic units, such as idioms, formulaic expressions, or lexical bundles. Three articles in the special issue investigate this domain (Bardovi-Harlig and Stringer, 2007, this issue; Shantz, 2017, this issue; Paquot, 2017, this issue). This area has been important because the formal (generative) approach mostly presumes a dichotomy between rules and lexical items, which are memory-based (e.g.…”
Section: Convergence and Divergencementioning
confidence: 99%
See 1 more Smart Citation
“…Among the existing studies on L2 formulaic language processing, researchers have found a number of factors that may influence the processing. These potential factors include language proficiency (e.g., Shantz, 2017;Siyanova-Chanturia, Conklin, & van Heuvan, 2011b; and L1 backgrounds (e.g., Carrol, Conklin, & Gyllstad, 2016;Sonbul & El-Dakhs, 2020;Wolter & Gyllstad, 2011). However, how these potential factors affect L2 formulaic language processing remains extremely unclear.…”
Section: List Of Tablesmentioning
confidence: 99%